1980
DOI: 10.1007/bf00313154
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes in multiple sclerosis

Abstract: Using a C1q binding test, circulating immune complexes (IC) were detected in 33.3% of sera from 138 patients and in 19.4% of 124 spinal fluid samples from patients with multiple sclerosis. Most often they occur in sera alone. As a rule their detectable amount is small in sera as well as in spinal fluids. IC were observed with equal frequency during acute exacerbations and in stable phases of the disease. In patients with early MS of less than 3 months duration, IC were detected only rarely, whereas their frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…The data indicated that circulating IC are present at increased levels in MS. The latter observation appears in previous reports (17,21) and it allows for the assumption that, although studies on CSF are of primary usefulness for an understanding of a disease whose alterations occur in the CNS, the pattern of IC levels in serum may also contain information on the immunological events involved in the disease. The Clq-BA test appears to be more sensitive for the detection of IC in CSF, the most significant correlation with clinical status being found by this method in the CSF from the relapsingremittent subgroup undergoing exacerbation, thus confirming Coyle's results (16).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The data indicated that circulating IC are present at increased levels in MS. The latter observation appears in previous reports (17,21) and it allows for the assumption that, although studies on CSF are of primary usefulness for an understanding of a disease whose alterations occur in the CNS, the pattern of IC levels in serum may also contain information on the immunological events involved in the disease. The Clq-BA test appears to be more sensitive for the detection of IC in CSF, the most significant correlation with clinical status being found by this method in the CSF from the relapsingremittent subgroup undergoing exacerbation, thus confirming Coyle's results (16).…”
Section: Discussionmentioning
confidence: 70%
“…This assumption is supported by such findings as the disfunction of T cell suppressor activity (3)(4)(5)(6)(7)(8)(9), the local synthesis of oligoclonal IgG in the CNS (6)(7)(8)(9), and the positive pattern of immunofluorescence suggesting IC deposition in the MS plaques (10,11). A correlation has been demonstrated between IC levels and the clinical course of the disease (13,16,17,20), and a relationship suggested with such other biological changes as barrier damage (12), lymphocyte population modifications (14), increased CSF T cells, and decreased T suppressor activity (20). Some early reports (12)(13)(14)(15)(16)(17) dealt with only one IC assay, whereas more recently (18)(19)(20)(21) results have been obtained by different assays, as suggested by WHO.…”
mentioning
confidence: 76%
“…However, it takes some 20 days of infection before this process happens, and thus some additional factor seems to be needed. It has been described for other diseases [47] and suggested for HAT [48] that antigen-antibody complexes (in this case the VSG-antibody complex) may concentrate inside the plexus, thus leading to inflammation and weakening of the endothelial fenestration. This could indeed account for the observed latency, although one might expect that blood cells would also enter the plexus in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of immunoglobulin G and complement factor Clq deposits in brain plaques (Woyciechowska & Brzosko 1977) further suggests a decisive role of IC in MS. Previously performed studies have reported weak but promising relations between the clinical appearance of MS, the occurrence of circulating immune complexes (Jans et al 1979, Patzold et al 1980, and fluctuations in the concentration of the complement factor C3 (Mar et al 1979).…”
mentioning
confidence: 99%
“…Immune complexes (IC) have been demonstrated in both the serum (Tachovsky et al 1976, Jans et al 1979, Patzold et al 1980) and cerebrospinal fluid (Deicher et al 1979, Patzold et al 1980, Glickmann et al 1980 of patients with multiple sclerosis (MS). Detection of immunoglobulin G and complement factor Clq deposits in brain plaques (Woyciechowska & Brzosko 1977) further suggests a decisive role of IC in MS.…”
mentioning
confidence: 99%